Modulation of interfacial interactions toward strong and tough cellulose nanofiber-based transparent thin films with antifogging feature. (15th February 2022) - Roy, Sunanda; Ghosh, Barnali Dasgupta; Goh, Kheng Lim; Muthoka, Ruth M.; Kim, Jaehwan
Abstract: Cross-linking is often performed to overcome the weak mechanical properties of native polymer films in order to expand their functional properties and applications. While this approach offers enhanced strength to the film, the film also suffers from low flexibility, low toughness and high brittleness. However, in view of the growing demand for strong and tough transparent thin films, this article reported our study to develop films made from cellulose nanofiber (CNF) via tailoring the interfacial bonding interactions through the application of glycerol (Gly) and glutaraldehyde (GA), which functioned as a plasticizer and cross-linking agent, respectively. Among the prepared films, the 10GA-8Gly-CNF film exhibited the best results with regard to the enhancement in the tensile strength (21.1%), Young's modulus (10.6%), elongation at break (100%) and toughness (32.7%), as compared to the native CNF film. Importantly, treating the surface of the film to radiofrequency oxygen plasma endowed the film with antifogging property, without compromising the optical clarity. Graphical abstract: Unlabelled Image